The Positive Political Dimensions of Regulatory Reform - Daniel B. Rodriguez (Washington University Law Quarterly, 1994)
This Article is concerned with two critical and interrelated questions in American public law. The first question is how the law should regulate politics. Specifically, how can legal doctrine be brought to bear on processes of politics and political decisionmaking in order to produce superior outcomes and to improve the operations of political process? The second question is how the law should deal with the modem regulatory process.
Keywords: Administrative law; Judicial review of administrative acts; Legal reform; United States; Administrative law reform; Political science